2021
DOI: 10.1371/journal.pone.0251242
|View full text |Cite
|
Sign up to set email alerts
|

An examination of school reopening strategies during the SARS-CoV-2 pandemic

Abstract: The SARS-CoV-2 pandemic led to closure of nearly all K-12 schools in the United States of America in March 2020. Although reopening K-12 schools for in-person schooling is desirable for many reasons, officials understand that risk reduction strategies and detection of cases are imperative in creating a safe return to school. Furthermore, consequences of reclosing recently opened schools are substantial and impact teachers, parents, and ultimately educational experiences in children. To address competing intere… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Indeed, schools in Europe's second wave operated under safety measures that some other organisations lacked: symptom screening, asymptomatic testing, contact tracing, sanitising, ventilation, distancing, reducing group sizes, and preventing the mixing of groups 41,45 . Our results are consistent with agent-based and compartmental modelling studies which predict large decreases in transmission in schools upon implementation of multiple safety measures 46,47 . Further, the effects of closures on transmission outside of the educational institutions might provide an additional explanation for the observed differences between the waves.…”
Section: Resultssupporting
confidence: 90%
“…Indeed, schools in Europe's second wave operated under safety measures that some other organisations lacked: symptom screening, asymptomatic testing, contact tracing, sanitising, ventilation, distancing, reducing group sizes, and preventing the mixing of groups 41,45 . Our results are consistent with agent-based and compartmental modelling studies which predict large decreases in transmission in schools upon implementation of multiple safety measures 46,47 . Further, the effects of closures on transmission outside of the educational institutions might provide an additional explanation for the observed differences between the waves.…”
Section: Resultssupporting
confidence: 90%
“…The US Center for Disease Control (CDC) has outlined five main mitigation strategies for school reopening, including; (1) consistent and correct use of masks, (2) adherence to social distancing measures, (3) hand hygiene and respiratory etiquette, (4) cleaning and disinfection; and (5) contact tracing in collaboration with the local health department [ 84 ]. In order to reduce the capacity of classrooms during school reopening, an earlier study also suggested the multiple cohorts rotation approach, in which in-person and remote classes would be conducted in parallel [ 85 ]. Mitigation strategies on the impact of the COVID-19 pandemic on teacher quality of life is also imperative to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Design and analysis issues apply, making it difficult to evaluate the impact of individual or combined measures (15). One study estimated that the combination of reduced class density, transmission mitigation measures (use of masks, desk shields, frequent surface cleaning, outdoor instruction), and early identification of active infections would reduce SARS-CoV-2 prevalence (16). Additionally, a study in Barcelona, Spain, found that transmission rates of SARS-CoV-2 among children were lower in summer schools applying IPC measures such as contact bubbles, hand hygiene, masks and outdoor activities, compared to the general population (17).…”
Section: Introductionmentioning
confidence: 99%